Simultaneous determination of furanocoumarins in infusions and decoctions from Carapia (Dorstenia species) by high-performance liquid chromatography - Cardoso, CAL; Vilegas, Wagner [UNESP]; Barison, A.; Honda, N. K. (Amer Chemical Soc, 2002)
The use of furanocoumarins, which are photosensitizing compounds, combined with exposure to UV-A radiation is a common treatment for vitiligo, psoriasis, and a number of other skin diseases. Although furanocoumarins plus UV-A treatment is highly effective, several studies have shown that exposure to high doses increases the risk to development of cutaneus carcinoma. Several Dorstenia species are used in folk medicine, mainly against skin diseases, because of the presence of biologically active compounds. We present here analysis of the chemical composition of furanocoumarins from infusion and decoction of Carapia (Dorstenia species), which is used in Brazil against several diseases. We have employed high-performance liquid chromatography (HPLC) procedures for the quantitative determination of psoralen, bergapten, and isopimpinellin. The contents of furanocoumarins revealed an insignificant difference between infusion and decoction. Dorstenia tubicina and D. asaroides contained psoralen and bergapten only in the rhizomes, whereas D. vitifolia shows solely isopimpinellin in both rhizomes and aerial parts.
Keywords: Dorstenia; furanocoumarins; HPLC; Carapia; psoralens